Eksistensi Lembaga Mediasi Sebagai Sarana Penyelesaian Sengketa Medis - Evalina Alissa; Sasmiar Sasmiar (Wajah Hukum, 2021)
This article discusses the existence of mediation institutions as a means of resolution in disputes, which discusses the legal basis and position of the mediation institution, the criteria or medical disputes and also the legal power of the mediating institution in the resolution of medical disputes. The research method used by the author is a doctrinal research method which is intended to find a legal principle, rule of law and legal doctrine in order to get answers to legal issues in the discussion in this article. Medical disputes arise due to different interpretations between health services and the patient/ patient's family in providing services to health. However, in the medical practice law, it is stated that the settlement of medical disputes can be done through litigation and submitting complaints to the Honorary Council of Indonesian Medical Disciplines and since the health law and the hospital law, mediation institutions have begun to be recognized as an institution that conducts medical work. the settlement process outside the judiciary and has the legal power of the mediation institution.